Pengaruh Persepsi Belajar Online Terhadap Kepuasan Dimediasi Kesiapan Belajar Pada Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret - Hanif, Eva Amalia; Sudarno, Sudarno; Sabandi, Muhammad (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the influence of perceptions of online learning on satisfaction mediated by online learning readiness among UNS Economics Education Students in online learning. This research is a survey-based quantitative descriptive approach. A proportional random selection procedure was used to select 205 UNS Economics Education students class 2019–2022 as the sample for this research. Data was collected using a questionnaire. Using the Confirmatory Factor Analysis (CFA) method for validity testing, Cronbach's Alpha for reliability testing, and hierarchical regression analysis for hypothesis testing, SPSS 23 software was used. Research findings show that: (1) online learning readiness has a positive and significant effect on student readiness in online learning; (2) online learning readiness has a positive and significant effect on UNS Economics Education student satisfaction; and (3) online learning readiness has a positive and significant effect on UNS Economics Education student satisfaction; and (4) online learning readiness mediates the relationship between perceptions of online learning and satisfaction of UNS Economics Education Students